95 BIAS “GURU-MURID” DAN BIAS “ORANG DALAM” DALAM STUDI-STUDI TENTANG KIAI - Mardimin, J.; Wiloso, Pamerdi Giri; Priyanto, Sony Heru (Universitas Kristen Satya Wacana, 2017)
Since 1980s, social role of the Kyai (Islamic Religious Teachers) has attracted many Indonesian dan International researchers. However, the research publications are mostly from the point of view of the Islamic researchers, therefore, they are less objective. We recognise „teacher-student relationship bias‟ and „insiders‟ point of view bias‟ because the researchers did backyard research. This article is meant to address the issue.